Scleraxis-Lineage Cells Contribute to Ectopic Bone Formation in Muscle and Tendon. (8th November 2016) - Agarwal, Shailesh; Loder, Shawn J.; Cholok, David; Peterson, Joshua; Li, John; Breuler, Christopher; Cameron Brownley, R.; Hsin Sung, Hsiao; Chung, Michael T.; Kamiya, Nobuhiro; Li, Shuli; Zhao, Bin; et al.
Abstract : The pathologic development of heterotopic ossification (HO) is well described in patients with extensive trauma or with hyperactivating mutations of the bone morphogenetic protein (BMP) receptor ACVR1 . However, identification of progenitor cells contributing to this process remains elusive. Here we show that connective tissue cells contribute to a substantial amount of HO anlagen caused by trauma using postnatal, tamoxifen-inducible, scleraxis-lineage restricted reporter mice ( Scx-creERT2/tdTomato fl/fl ). When the scleraxis-lineage is restricted specifically to adults prior to injury marked cells contribute to each stage of the developing HO anlagen and coexpress markers of endochondral ossification (Osterix, SOX9). Furthermore, these adult preinjury restricted cells coexpressed mesenchymal stem cell markers including PDGFRα, Sca1, and S100A4 in HO. When constitutively active ACVR1 ( caACVR1 ) was expressed in scx-cre cells in the absence of injury ( Scx-cre/caACVR1 fl/fl ), tendons and joints formed HO. Postnatal lineage-restricted, tamoxifen-inducible caACVR1 expression ( Scx-creERT2/caACVR1 fl/fl ) was sufficient to form HO after directed cardiotoxin-induced muscle injury. These findings suggest that cells expressing scleraxis within muscle or tendon contribute to HO in the setting of both trauma or hyperactive BMP receptor (e.g., caACVR1) activity.